Chinese Citrus Fly, Bactrocera minax (Enderlein) Oviposition Periods in Citrus Orchard, Nepal - Adhikari, Debraj; Thapa, Resham Bahadur; Joshi, Samudra Lal; Du, Jason Jinping (Journal of the Plant Protection Society, 2023)
Chinese citrus fly, Bactrocera minax (Enderlein) is a major pest of citrus fruits that causes significant fruit losses in citrus orchards in Nepal, China, Bhutan and India. In 2021, a field study was conducted to know the oviposition period of this pest in a sweet orange orchard in Sindhuli, Nepal. The pest deposits its eggs on 25-50 mm citrus fruits during June-July. The timing of egg laying is crucial in designing and deploy adult fly management such as protein bait in citrus orchards.